Personal and household items. (Chicago : World Book, 2009)
"An exploration of the transformative impact of inventions and discoveries in agriculture. Features include fact boxes, sidebars, biographies, and a timeline, glossary, list of recommended reading and Web sites, and index"--Provided by publisher
Scissors -- Toothbrush -- Soap -- Glass mirror -- Fork -- Eyeglasses -- Thermometer -- Wristwatch -- Battery -- Light bulb -- Canned foods -- Sewing machine -- Blue jeans -- Zipper -- Crayons -- Vacuum cleaner -- Microwave oven -- Instant noodles -- Electronic games -- Important dates in personal and household items.
Includes bibliographical references and index.
Keywords: TECHNOLOGY -- JUVENILE LITERATURE